Transcriptional responses of Streptococcus gordonii and Fusobacterium nucleatum to coaggregation - Mutha, Naresh V.R.; Mohammed, Waleed K.; Krasnogor, Natalio; Tan, Geok Yuan Annie; Choo, Siew Woh; Jakubovics, Nicholas Stephen (Wiley, 2018)
Cell-cell interactions between genetically distinct bacteria, known as coaggregation, are important for the formation of mixed-species biofilms such as dental plaque. Interactions lead to gene regulation in the partner organisms that may be critical for adaptation and survival in mixed-species biofilms. Here, gene regulation responses to coaggregation between Streptococcus gordonii and Fusobacterium nucleatum were studied using dual RNA-Seq. Initially, S. gordonii was shown to coaggregate strongly with F. nucleatum in buffer or human saliva. Using confocal laser scanning microscopy and transmission electron microscopy, cells of different species were shown to be evenly distributed throughout the coaggregate and were closely associated with one another. This distribution was confirmed by serial block face sectioning scanning electron microscopy, which provided high resolution three-dimensional images of coaggregates. Cell-cell sensing responses were analysed 30 minutes after inducing coaggregation in human saliva. By comparison with monocultures, 16 genes were regulated following coaggregation in F. nucleatum whereas 119 genes were regulated in S. gordonii. In both species, genes involved in amino acid and carbohydrate metabolism were strongly affected by coaggregation. In particular, one 8-gene operon in F. nucleatum encoding sialic acid uptake and catabolism was up-regulated 2- to 5-fold following coaggregation. In S. gordonii, a gene cluster encoding functions for phosphotransferase system-mediated uptake of lactose and galactose was down-regulated up to 3-fold in response to coaggregation. The genes identified in this study may play key roles in the development of mixed-species communities and represent potential targets for approaches to control dental plaque accumulation.